1989
DOI: 10.3109/08958378909145229
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Inhalation Study in Rats, Using a Second Prototype of a Cigarette that Heats Rather than Burns Tobacco

Abstract: Sprague-Dawley rats were exposed nose-only for 1 h/day on weekdays for 13 weeks to the smoke from test and reference cigarettes. The test cigarette was a new prototype: the tobacco is heated rather than burned. The University of Kentucky lR4F cigarette was used as a reference. The exposures used were around 25% higher than those used in earlier studies, and for the test cigarette the resulting blood carboxyhemoglobin concentrations approached those associated with death (62 + %). The smoke from the reference c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 13 publications
5
12
1
Order By: Relevance
“…Our studies (5,6,18,22) have supported the conclusion of Lewis (11,13) and Gopinath et al (8) that the epithelium lining the base of the epiglottis is the area of the laryngeal mucosa in laboratory rodents most susceptible to changes induced by inhaled irritants.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our studies (5,6,18,22) have supported the conclusion of Lewis (11,13) and Gopinath et al (8) that the epithelium lining the base of the epiglottis is the area of the laryngeal mucosa in laboratory rodents most susceptible to changes induced by inhaled irritants.…”
Section: Discussionsupporting
confidence: 88%
“…As in the nose, the predilection of these sites for lesions in rodents is probably due to airflow characteristics and regional epithelial sensitivity (4,8,11,13 (5,6,22) or glycerol (18). Sources, housing, and necropsy procedures for the animals of these studies have been reported previously (5,6,18,22 …”
Section: Introductionmentioning
confidence: 99%
“…For the highest dose level of each cigarette and for the sham-exposed group, a satellite group (10 male and 10 female rats) was kept without treatment for 42 days after inhalation. This period is deemed sufficiently long to investigate the reversibility of the findings typically seen in subchronic mainstream smoke inhalation studies (Coggins et al, 1989b).…”
Section: Experimental Experimental Designmentioning
confidence: 99%
“…Such designs, in which the burning tobacco as the energy source is replaced by a slowly and continuously smoldering carbon heat source, yield smoke aerosols composed primarily of water and glycerine. Subsequent designs again burned some tobacco (Coggins et al, 1989b), most likely to enhance taste.…”
Section: Introductionmentioning
confidence: 99%
“…The comparative sister chromatid exchange assay with smoke condensate of the cigarettes used in (351) and (352) were absent or (primarily in the larynx) substantially reduced and completely reversible in the animals exposed to the smoke of the novel cigarette type. In an inhalation study of similar experimental design (360) with mentholated cigarettes of the traditional and the novel type, the response pattern observed after smoke exposure and the reversibility of lesions were the same as with the comparable non-mentholated test pieces (359). The addition of menthol did not influence the substantial difference in biological effects noted between the two types of cigarettes.…”
Section: Mentholmentioning
confidence: 81%